The Impact of Angle Lambda on Patient Satisfaction after Optiflex Trio Trifocal Intraocular Lens Implantation - Sultan Kaya Ünsal; Ertan Sunay (Journal of Ophthalmology)
Purpose. To evaluate the vision-related quality of life (QOL), visual acuities, and refractive outcomes of patients with different angle lambda (λ) after a trifocal intraocular lens (IOL) implantation at Veni Vidi Eye Hospital, İstanbul, Turkey. Methods. This retrospective, nonrandomized, and noncomparative case series included patients who had phacoemulsification bilaterally with the implantation of a trifocal IOL (Optiflex Trio) and responded to a vision-related QOL questionnaire measuring patient satisfaction. The patients were divided into two groups according to the angle λ with a cutoff value of 0.5 mm. Evaluations were conducted to examine the monocular visual acuities, spherical equivalents, corneal astigmatism measured 3 months after surgery, and outcomes of the QOL questionnaire in the two groups. Results. The study examined 130 eyes from 65 patients aged from 41 to 78 years old. There were no statistically significant differences between the two groups at 3 months after surgery in terms of uncorrected distance visual acuity (UDVA), monocular uncorrected intermediate visual acuity (UIVA), monocular uncorrected near visual acuity (UNVA), spherical equivalent, and corneal astigmatism (P>0.05). Patients with a greater angle λ had significantly more difficulty going out to see movies, plays, or sporting events (P=0.02), driving at night (P=0.002), and driving in difficult conditions (P<0.001) than patients with a lower angle λ. Conclusions. The Optiflex Trio showed good results in terms of visual acuity at all distances, positive refractive outcomes, and high patient satisfaction in daily life according to the QOL questionnaire. An angle λ greater than 0.5 mm may potentially cause dysphotopsia symptoms, especially during nighttime activities.